Política de indexação: discussões sobre bibliotecas da UFPA - SANTOS, Lain Mendonça dos (2017)
It is of great influence in the results coming from the search of the user in an information unit, the guidelines that guide the work of the librarian / indexer, since they help in the determination of the consistency in the indexation. The elements, variables and requirements of the Indexing Policy contribute to achieve search results that better meet the needs of the user community, as it values the interests of the user, satisfying the issues raised by the demand. In this sense, the present research develops the topic Indexing Policy: discussions in UFPA libraries. Intends to discuss the Policy of Indexation in University Libraries, to verify if there is the adoption of this policy in the UFPA libraries and the possible evaluation of the practices in Indexing Policy. It develops a study to identify aspects of the Indexing Policy practiced in the sector libraries and Central Library. It uses a bibliographical review for theoretical basis and the questionnaire as a tool for data collection. The data analysis revealed the partial practice of Indexing Policy in the libraries studied, highlights the initiative of professionals responsible for such practices. It concludes by highlighting the importance and necessity of the implementation of the Indexing Policy in the context of the University Library.